Analisis Penerapan Keselamatan Dan Kesehatan Kerja (K3) Dengan Metode Fault Tree Analysis (FTA) Guna Meningkatkan Produktivitas Kerja Di PT. Ciptaunggul Karya Abadi - Andika Rafli Kusnendar; Dene Herwanto; hamdani dani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Ciptaunggul Karya Abadi is a manufacturing industry in the field of manufacturing spare parts that produces stamping parts (cold forming), tools, and dies. One of the problems faced by this company is the low productivity of employees due to the influence of poor implementation and implementation of K3. The research is aimed at analyzing work safety in order to increase productivity. Data processing in this study used the Safe T Score method (safe T score) to determine the effect of accident rates on work productivity. Then the Fault Tree Analysis (FTA) method is used to analyze the causes of potential accidents. The research results obtained are the Safe T Score (safe t value) in the period 2019 to 2020 which is -0.41 which means that the situation is improving. in the year 2019-2020. From the results obtained in the FTA model, it can be seen the causes that caused the accident problem that occurred at PT. Ciptaunggul Karya Abadi, which is falling while working, being hit by raw materials/finished products, being hit by a fire and being pinched by a machine. Keywords: Fault Tree Analysis (FTA); Occupational Health and Safety (K3); Productivity;